2022
DOI: 10.1371/journal.pone.0262952
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and antimicrobial susceptibility profile of uropathogens

Abstract: The uropathogens is the main cause of urinary tract infection (UTI). The aim of the study was to isolate bacteria from urine samples of UTI patients and find out the susceptibility of isolated bacteria. Bacteria were identified using both conventional and molecular methods. Sanger sequence procedure used for 16S ribosomal RNA and phylogenetic analysis was performed using Molecular Evolutionary Genetics Analysis (MEGA-7) software. In this study, Escherichia coli, Klebsiella pneumonia, Staphylococcus were report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The predominant pathogenic bacteria identified were E. coli (50.0%), E. faecium (15.6%), E. faecalis (9.6%), K. pneumoniae (6.8%), P. aeruginosa (3.5%), A. baumannii (2.7%), S. agalactiae (2.5%), S. aureus (2.1%) and P. mirabilis (1.2%). These findings align with those of previous studies (24)(25)(26). Another similar study by Faine et al (27) showed that among the patients with positive urine cultures, 84.7% had cultures that grew Enterobacterales, with E. coli (63.2%) being the most common pathogen isolated.…”
Section: Discussionsupporting
confidence: 93%
“…The predominant pathogenic bacteria identified were E. coli (50.0%), E. faecium (15.6%), E. faecalis (9.6%), K. pneumoniae (6.8%), P. aeruginosa (3.5%), A. baumannii (2.7%), S. agalactiae (2.5%), S. aureus (2.1%) and P. mirabilis (1.2%). These findings align with those of previous studies (24)(25)(26). Another similar study by Faine et al (27) showed that among the patients with positive urine cultures, 84.7% had cultures that grew Enterobacterales, with E. coli (63.2%) being the most common pathogen isolated.…”
Section: Discussionsupporting
confidence: 93%
“…The results of our study concluded that female patients had higher incidences of UTIs (67.47%, 56/83) compared to male (32.53%, n = 12/83) patients living in the Lower Dir (Table 1). Previous studies also reported that females have higher incidences of UTIs than males within a given study population (frequency rate: 73.57% and 36.14%, respectively) [43][44][45][46]. This high incidence of UTIs in females is due to physiological changes during pregnancy, parity (number of pregnancies a person has had), hormonal changes and immune responses [47][48][49].…”
Section: Discussionmentioning
confidence: 77%
“…Uropathogenic Escherichia coli (UPEC) and Staphylococcus aureus are frequently detected in patients with indwelling urinary tract devices [3][4][5][6]. Urinary tract infections (UTIs) are considered to be the most common bacterial infections, affecting around 150-250 million people each year worldwide.…”
Section: Introductionmentioning
confidence: 99%